Test charge driven response of a dusty plasma with polarization force - Ali, S.; Masood, W.; Singh, K.; Jahangir, R. (Frontiers in Astronomy and Space Sciences, 2022)
By using the framework of kinetic model, the test charge driven response of a dusty plasma is evaluated in the presence of polarization force. The plasma containing electrons, singly ionized positive ions, and highly charged negative dust particulates is known as a dusty plasma, which can be perturbed by a test particle of charge qT moving with velocity vT along the z-axis. The polarization force purely comes from the high charging state of micron-sized dust particles, causing a deformation of shielding length due to density gradient and modifying the collective motion and particulates’ acceleration. The application of Fourier transformation technique to the set of dynamical equations may result in the shielded potential for a test charge with a modified dielectric constant. Several possibilities have been explored to evaluate the shielded potentials by imposing different conditions on the test charge speed in comparison with the thermal speeds of plasma species. It is found that the profiles of wakefield, Debye-Hückel and farfield (FF) potentials are strongly modified by the polarization force coefficient via the dust charging state and dust concentration. The present findings are useful in the study of strongly coupled dusty plasma, where micron-sized negatively charged dust grains are characterized by a high charging state.